Effect of PDCA-optimized good limb positioning on hemiparetic rehabilitation outcomes in acute cerebral infarction - Liu, Wei; Yao, Guangyan; Song, Zhihui; He, Xin (Frontiers in Neurology, 2025)
BackgroundProper limb positioning plays a vital role in the early rehabilitation of patients with acute cerebral infarction (ACI), preventing complications such as muscle atrophy and joint contractures while promoting functional recovery. However, inconsistent implementation limits its effectiveness. This study evaluates the impact of the Plan-Do-Check-Act (PDCA) cycle management model in optimizing good limb positioning and improving rehabilitation outcomes.MethodsA prospective cohort study was conducted involving 300 hemiplegic ACI patients, with 150 patients receiving standard limb positioning care (control group) and 150 patients treated using the PDCA-optimized protocol (intervention group). The study was approved by The Ethics Committee of Central Hospital Affiliated to Shandong First Medical University (approval number: 20241104006). Outcomes included adherence rates, self-efficacy, quality of life (SF-36), activities of daily living (ADL), and secondary complications such as limb spasticity.ResultsThe intervention group demonstrated significantly higher adherence rates (88.0% vs. 48.0%, p < 0.001) and improved rehabilitation outcomes, including increased self-efficacy (25.0 vs. 17.0, p < 0.001), better quality of life (66.5 ± 13.8 vs. 61.7 ± 17.2, p < 0.001), and enhanced ADL scores (62.2 ± 10.2 vs. 52.8 ± 9.9, p < 0.01). Median hospital stay was reduced (10 days vs. 12 days, p = 0.001), and limb spasticity incidence was lower in the intervention group (p = 0.001). No significant differences in discharge NIHSS scores were observed.ConclusionThe PDCA cycle significantly enhances the implementation of good limb positioning, improving functional recovery, reducing secondary complications, and optimizing rehabilitation timelines for ACI patients. This study highlights the utility of PDCA in standardizing care practices and promoting better clinical outcomes. Further research should explore its broader application in diverse clinical settings.